A gigantic new dinosaur from Argentina and the evolution of the sauropod hind foot - Gonzalez Riga, Bernardo Javier (2016)
Titanosauria is an exceptionally diverse, globally-distributed clade of sauropod dinosaurs that includes the largest known land animals. Knowledge of titanosaurian pedal structure is critical to understanding the stance and locomotion of these enormous herbivores and, by extension, gigantic terrestrial vertebrates as a whole. However, completely preserved pedes are extremely rare among Titanosauria, especially as regards the truly giant members of the group. Here we describe Notocolossus gonzalezparejasi gen. et sp. nov. from the Upper Cretaceous of Mendoza Province, Argentina. With a powerfully-constructed humerus 1.76m in length, Notocolossus is one of the largest known dinosaurs. Furthermore, the complete pes of the new taxon exhibits a strikingly compact, homogeneous metatarsus - seemingly adapted for bearing extraordinary weight - and truncated unguals, morphologies that are otherwise unknown in Sauropoda. The pes underwent a near-progressive reduction in the number of phalanges along the line to derived titanosaurs, eventually resulting in the reduced hind foot of these sauropods.